Sub-Acute Toxicity Test of Red Betel Leaves (Piper crocatum) on Liver Function in Male White Mice (Mus musculus) Using SGPT Test - Andriani, Medi; Putra, Rizky Yulion; Asnadewi, Veni (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: This research aims to investigate the sub-acute toxicity of red betel leaves (Piper crocatum) on liver function in male white mice (Mus musculus) using a serum glutamic-pyruvic transaminase (SGPT) test on a clinical photometer instrument. Methods: This research aims to investigate the sub-acute toxicity of red betel leaves (Piper crocatum) on liver function in male white mice (Mus musculus) using a test serum Glutamic Pyruvic Transaminase (SGPT) assay on a clinical photometer instrument. In this study, an experimental method was employed using a randomized block design, with 72 mice serving as research subjects and divided into eight treatment groups. Group 1 was given 0.5% Na CMC, group 2 as a positive control; group 3 was given a comparison of metformin; group 4 was given an extract with a dose of 100 mg/KgBB, group 5 was given the N-Hexane fraction with a dose of 100 mg/KgBB, group 6 was given the Ethyl Acetate fraction with a dose of 100 mg/KgBB, group 7 was given the N-Butanol fraction with a dose of 100 mg/KgBB, group 8 was given the Residual Water Fraction with a dose of 100 mg/KgBB, the treatment was carried out for 2, 4, 6 days, in the SGPT test used was serum. Results: The administration of extracts and fractions to animals did not cause Subacute Toxicity effects on the livers of male white mice. Looking at the SGPT (Serum Glutamic Pyruvic Transaminase) parameters, the activity of which was still within normal conditions, namely 25-200 µ/l. Conclusions: did not show any Subacute Toxicity effects as seen from the activity of the SGPT enzyme in the blood of male white mice (Mus musculus).